(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
The main objective of this study is to examine the effect of selected board attributes on tax aggressiveness of quoted insurance companies in Nigeria. Specifically, the study examines the combined effect of female directors and board financial expertise on tax aggressiveness of quoted insurance companies in Nigeria. Tax aggressiveness was measured using effective tax rate while female directors and financial expertise were measured using proportion of female directors on the board to the total number of independent directors and proportion of financial experts on the board to the total number of independent directors respectively. This study uses the longitudinal research design. The population of the study is the entire twenty-three listed companies in the Nigerian insurance sector. The sample size of twenty-two was selected after eliminating one without complete data. Data were sourced from the annual financial statements of the listed insurance companies for the period 2011-2022. To be able to examine the effect of female directors and financial expertise on tax aggressiveness, the study used panel multiple regression model for the analysis. The result of the study shows that female directors have negative and insignificant effect on tax aggressiveness. However, the study finds statistical evidence which suggests that boards financial expertise has significant effect on tax aggressiveness in the insurance sector. From the findings, it was concluded that board attributes have strong explanatory power on tax aggressiveness. The study recommends that since management could aspire to avoid more taxes, because they estimate the tax benefits too high, more external board members with accounting and corporate reporting knowledge should be admitted on the boards to curtail managerial aggressive tax planning.